Dissimilatory sulphate reduction in hypersaline coastal pans: an integrated microbiological and geochemical study. Issue 3 (4th February 2013) - Roychoudhury, A. N.; Cowan, D.; Porter, D.; Valverde, A.
Abstract Here, we report on the spatial and temporal variation in sulphate‐reducing bacterial community structure and activity in three hypersaline coastal pans. Community structure was determined using denaturing gradient gel electrophoresis (DGGE). Cluster analysis of DGGE patterns indicated that similar microbial populations were generally found in individual pans but varied from one pan to the other. Sulphate reducing bacteria (SRB) were quantified by competitive polymerase chain reaction based on the amplification of the dsrAB genes. Cell numbers and in situ sulphate reduction activities varied between seasons and pans but in general showed low variation in depth. Sulphate reduction activity was not correlated with microbial population size indicating that community composition is relevant for specific microbial processes. Principal component analysis coupled with correlation analyses suggested that salinity, sulphate concentration, C/N ratio and pH were the most important factors in explaining variations in SRB community composition. Most sequences derived from DGGE amplicons belonged to members of the Desulfobacteraceae and Desulfohalobiaceae families.